Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Chapter 8 - Complex Numbers, Polar Equations, and Parametric Equations - Section 8.6 Parametric Equations, Graphs, and Applications - 8.6 Exercises - Page 404: 27

Answer

(a) We can see the graph below. (b) $y = x - 6$
1529562172

Work Step by Step

$x = t+2$ $y = t-4$ (a) t = -2: $x = (-2)+2 = 0$ $y = (-2)-4 = -6$ t = -1: $x = (-1)+2 = 1$ $y = (-1)-4 = -5$ t = 0: $x = (0)+2 = 2$ $y = (0)-4 = -4$ t = 1: $x = (1)+2 = 3$ $y = (1)-4 = -3$ t = 2: $x = (2)+2 = 4$ $y = (2)-4 = -2$ We can see the graph below. (b) $x = t+2$ $t = x-2$ $y = t-4$ $y = (x-2)-4$ $y = x - 6$
Small 1529562172
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.